A STUDY ON THE THIRD YEAR STUDENTS’ PERCEPTION ON ONLINE LEARNING AT SMPN 13 PEKANBARU - Farhana, Qinthara Afni; Purwanti, Indah Tri; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was aimed to investigate the third year students' perception in using online learning in SMPN 13 Pekanbaru. The population of this research was 350 total number of third year students of SMPN 13. This study only took 105 students from class 9.2, 9.4, and 9.6 out of 350 students as the sample of this research. The researcher used a questionnaire and interview to collect the data of students’ perception on online learning. There were 25 items for the questionnaire. The second instrument for this research was an interview. The researcher conducted a structured interview and prepared 5 questions to be asked to the respondent. There were 3 students from each class as interviewers. The highest score of indicator comes from students’ perception on students’ convenience in online learning indicator and students’ perception on motivation to learn online indicator which is categorized in high criteria for both indicators. The researcher concluded that the average score of the students’ perception on online learning is 3,22 and it is categorized as moderate criteria. From interviews results, the researcher found some responses from respondents toward online learning. There was positive and negative feedback from the students that they felt during online learning. They also assumed that online learning has more disadvantages than offline learning such as not understandable, lack of communication, external distraction and technology and network problems.Key Words: Study, Perception, Online Learning